Empirical Evidence on the Dynamics of Incentive Plans - Takao Kato; Antti Kauhanen; Julia Salmi (The Research Institute of the Finnish Economy (ETLA), 2013)
Using three different waves of a survey on compensation practices from 2005, 2007, and 2010, we study the dynamics of incentive plans. We describe that firms frequently discontinue incentive plans and often change performance measures and organizational levels of performance measurement. The results show that incentive plans are dynamic in nature, but that the dynamics are difficult to explain. The power of the leading theoretical explanations for these changes, i.e., turbulence in the operating environment and learning about performance measures, is not strong.
Keywords: 330